Luciferase‐Induced Photouncaging: Bioluminolysis. Issue 45 (20th September 2019) - Chang, Dalu; Lindberg, Eric; Feng, Suihan; Angerani, Simona; Riezman, Howard; Winssinger, Nicolas
Abstract: Bioluminescence resonance energy transfer (BRET) has been widely used for studying dynamic processes in biological systems such as protein–protein interactions and other signaling events. Aside from acting as a reporter, BRET can also turn on functions in living systems. Herein, we report the application of BRET to performing a biorthogonal reaction in living cells; namely, releasing functional molecules through energy transfer to a coumarin molecule, a process termed bioluminolysis. An efficient BRET from Nanoluc‐Halotag chimera protein (H‐Luc) to a coumarin substrate yields the excited state of coumarin, which in turn triggers hydrolysis to uncage a target molecule. Compared to the conventional methods, this novel uncaging system requires no external light source and shows fast kinetics ( t 1/2 <2 min). We applied this BRET uncaging system to release a potent kinase inhibitor, ibrutinib, in living cells, highlighting its broad utility in controlling the supply of bioactive small molecules in vivo. Abstract : Let there be light ! The unmasking of coumarin‐caged molecules was achieved by a resonance energy transfer (BRET) from a luciferase. The reaction was shown to proceed quickly ( t 1/2 <2 min) in the presence of the luciferase substrate.